2020
DOI: 10.3390/biomedicines8060172
|View full text |Cite
|
Sign up to set email alerts
|

False Myths versus Medical Facts: Ten Common Misconceptions Related to Dry Eye Disease

Abstract: Since the first definition of dry eye, rapid progress has been made in this field over the past decades that has guided profound changes in the definition, classification, diagnosis and management of the disease. Although dry eye is one of the most frequently encountered ocular conditions, various “old” misconceptions persist, in particular among comprehensive ophthalmologists not specialized in ocular surface diseases. These misconceptions hamper the correct diagnosis and the proper management of dry eye in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…At the same time, ocular surface disease can have a negative impact on surgical outcomes; therefore, optimisation of the ocular surface prior to surgery is important to ensure better outcomes. 70,[79][80][81] These data support the panel consensus on continuing CsA treatment if a patient with DED is undergoing surgery.…”
Section: Csa Treatment Tapering and Discontinuationsupporting
confidence: 65%
“…At the same time, ocular surface disease can have a negative impact on surgical outcomes; therefore, optimisation of the ocular surface prior to surgery is important to ensure better outcomes. 70,[79][80][81] These data support the panel consensus on continuing CsA treatment if a patient with DED is undergoing surgery.…”
Section: Csa Treatment Tapering and Discontinuationsupporting
confidence: 65%
“…These results advocate the clinical utility of a consensus of signs, which better captures the entire disease and discourages dependence on symptoms alone [77]. This finding differs from that reported by Schein et al [19], who found no association between the presence of more frequent symptoms and a lower Schirmer result, regardless of whether the analysis was based on mean scores with a cut-off value of five or a cut-off value of seven [77]. Their sensitivity and specificity in the detection of symptomatic subjects was low [72,78,79].…”
Section: Discussionmentioning
confidence: 69%
“…This is believed to be due to the instability of the tear film in affected patients and can be used as a diagnostic hallmark of DED [32,63,76]. These results advocate the clinical utility of a consensus of signs, which better captures the entire disease and discourages dependence on symptoms alone [77]. This finding differs from that reported by Schein et al [19], who found no association between the presence of more frequent symptoms and a lower Schirmer result, regardless of whether the analysis was based on mean scores with a cut-off value of five or a cut-off value of seven [77].…”
Section: Discussionmentioning
confidence: 91%
“…Given that patients usually do not understand that DED is a chronic condition and are inclined to underestimate the importance of treatment, it was stressed that diminutive words such as “droplets” should be avoided in favor of more appropriate terms such as “tear substitute” or “artificial tear”. The posology regimen “as needed” was also criticized because it suggests that patients can autonomously decide when a symptom should be treated, whereas there is a need for continuous ocular surface nutrition regardless of patient’s ocular discomfort [ 39 ]. It was also considered important to explain that treatment is not prescribed to treat the perceived symptom but in order to treat the underlying cause of the symptom.…”
Section: Resultsmentioning
confidence: 99%